2010
DOI: 10.1001/archinternmed.2010.78
|View full text |Cite
|
Sign up to set email alerts
|

Mood Food

Abstract: Background Much lore but few studies describe a relation of chocolate to mood. We examined the cross-sectional relationship of chocolate consumption with depressed mood in adult men and women. Methods A sample of 1018 adults (694 men and 324 women) from San Diego, California, without diabetes or known coronary artery disease was studied in a cross-sectional analysis. The 931 subjects who were not using antidepressant medications and provided chocolate consumption information were the focus of the analysis. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 23 publications
1
17
0
1
Order By: Relevance
“…This explanation is supported by findings in adolescents indicating that the highest quartile for confectionery intake was associated with higher depression scores [7]. Our result also corresponds with a cross-sectional study of 1,018 adults that found higher depression scores to be related to greater chocolate consumption [13]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This explanation is supported by findings in adolescents indicating that the highest quartile for confectionery intake was associated with higher depression scores [7]. Our result also corresponds with a cross-sectional study of 1,018 adults that found higher depression scores to be related to greater chocolate consumption [13]. …”
Section: Discussionsupporting
confidence: 91%
“…In these studies, depression was associated with a lower healthy diet score [3,8] and with a Western dietary pattern consisting of increased intakes of takeaway foods, confectionery and red meat [7]. Similar relationships with depression were also reported from several adult studies investigating healthy dietary patterns [9,10], unhealthy dietary patterns [11,12,13] and diet quality [14]. …”
Section: Introductionmentioning
confidence: 69%
“…Others have similarly shown that these individuals report greater consumption of high calorie foods (e.g. ready-to-eat and fast foods) (Liu et al, 2007) and high chocolate consumption (Rose, Koperski, & Golomb, 2010). In general, our findings examining depressive symptoms and intake of high calorie foods were in the expected direction.…”
Section: Discussionmentioning
confidence: 96%
“…Individuals with depressive symptoms may consume higher amounts of highly palatable foods (e.g. high sugar and high fat) as a way of regulating dopamine availability and ultimately mood (Corsica & Pelchat, 2010; Rose, et al, 2010). Repeated stimulation of the reward pathways through highly palatable food may lead to dopamine dysregulation and overeating (Fulton, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Chocolate consumption in this sample was previously associated unfavorably with mood. 6 Because mood could serve as a confounder or mediator, analyses were conducted with and without CES-D adjustment.…”
Section: Methodsmentioning
confidence: 99%